Pengaruh Budaya Organisasi terhadap Keberhasilan Pengembangan E-Government - Togar A. Napitupulu; Desmi Avicena Medina (Bina Nusantara University, 2012)
Since the issuance of Presidential Instruction No. 3 / 2003 and Law No. 14/2008, government agencies ranging from central to district level are trying to be the leader in implementing e-government in meeting the information disclosure to the public. Up to this moment, the Ministry of Religious Affairs is still far from perfect in implementing e-Governement as can be seen that very few of them using e-mail as a means of communication and website as a tool to provide better information to the public as well as to support internal organization activities The objective of this research is to study the impact of organization's culture on the successful development and implementation of e-government using measurement method of organizational culture developed by Luthans (1998) where organizational culture is the norms and values that drive the behavior of members of the organizatio having behavioural dimensions of people, structure, technology, and the organization’s environment. The e-Government itself is measured by its benefits. Using Structural Equation Model (SEM) it was found that the organizational culture significantly influence the successful development of and implementation of e-Government where the most significant factors are people dimension and the external environment.